Comparing instructor‐led, video‐model, and no‐instruction control tutorials for creating single‐subject graphs in Microsoft Excel: A systematic replication and extension - Zonneveld, Kimberley L. M.; Cox, Alison D.; Asaro, Madeline M.; Hranchuk, Kieva S.; Alami, Arezu; Kelly, Laura D.; Frijters, Jan C. (Journal of applied behavior analysis, 2024)
Visual inspection of single‐subject data is the primary method for behavior analysts to interpret the effect of an independent variable on a dependent variable; however, there is no consensus on the most suitable method for teaching graph construction for single‐subject designs. We systematically replicated and extended Tyner and Fienup (2015) using a repeated‐measures between‐subjects design to compare the effects of instructor‐led, video‐model, and no‐instruction control tutorials on the graphing performance of 81 master's students with some reported Microsoft Excel experience. Our mixed‐design analysis revealed a statistically significant main effect of pretest, tutorial, and posttest submissions for each tutorial group and a nonsignificant main effect of tutorial group. Tutorial group significantly interacted with submissions, suggesting that both instructor‐led and video‐model tutorials may be superior to providing graduate students with a written list of graphing conventions (i.e., control condition). Finally, training influenced performance on an untrained graph type (multielement) for all tutorial groups.